Analisis Portofolio Optimal Dengan Menggunakan Model Indeks Tunggal Untuk Pengambilan Keputusan Investasi - Endriana Widhaningayu; Herma Wiharno (Program Studi Akuntansi, Universitas Kuningan, 2016)
The purpose of this study was to examine and determine to determine the proportion of shares on the optimal portfolio is formed, to determine the level expected benefits and risks of the portfolio is formed, and to know the difference in average frequency trading group candidate shares optimal portfolio with non-stock group candidate optimal portfolio. The sampling method used in this research is purposive sampling method sampling method based on certain criteria. The number of samples used in this study based on the criteria as much as 28 industry companies. The study was conducted in the period August 2011 to January 2014. So the observation data obtained by 65 observation data. Hypothesis testing is done by using t test. The result of the single index model showed that Large expected returns in the optimal portfolio E (Rp) 6.1733% 1.9159 with risk. Analysis of the different test by test t t generate profit amounted to 0.895 risks and to return 2,367, while t table at a significance level of 0.05 and df: 25, amounting to 2.05954 which may mean that the risk of assuming no significant difference while on return assumptions are no significant differences between the candidates forming the optimal portfolio shares with non-candidate stock portfolio.Keywords: LQ 45 Index, Single Index Model, Optimal Portofolio